Dual series equations involving generalized Laguerre polynomials - B. M. Singh; J. Rokne; R. S. Dhaliwal (International Journal of Mathematics and Mathematical Sciences)
An exact solution is obtained for the dual series equations involving generalized Laguerre polynomials.